Astragalus polysaccharide supplementation improves production performance, egg quality, serum biochemical index and gut microbiota in Chongren hens. (26th April 2021) - Lv, Hongwei; Tang, Yanqiang; Zhang, Haihan; Li, Siming; Fan, Zhiyong
Abstract: This research aimed to determine whether the astragalus polysaccharide (AP) can improve the production performance and gut microbiota in Chongren hens.120 Chongren hens (240‐d old) were randomly allocated into 4 treatments with 30 hens and fed with a control basal diet (CON) or CON supplemented with the different levels of AP (100, 200, and 400 mg/kg) for 56 d. The egg production and feed conversion ratio were decreased ( p  < .05) with the levels of AP. The yolk weight, yolk color, eggshell thickness, eggshell redness index and egg shell yellowness were increased ( p  < .05). AP supplementation increased CAT and T‐AOC and SOD, and decreased MDA ( p  < .05). Supplementation of AP decreased IL‐2, IL‐6 and TNF‐α levels ( p  < .05), but increased the IL‐4 level in the liver ( p  < .05). The villus heights of duodenum, jejunum ileum, the crypt depth and V/C in the jejunum were increased ( p  < .05). Dietary supplementation of 200 mg/kg AP increased (P relative abundances of Firmicutes and Lactobacteriaceae in the cecum of Chongren hens. In conclusion, addition of AP improved the production performance, egg quality, antioxidant function, and intestinal morphology in hens, which might be associated with the gut microbiota.